Theodicy and Crisis: Explaining Variation in U.S. Believers' Faith Response to the COVID-19 Pandemic. (10th November 2021) - Beyerlein, Kraig; Nirenberg, David; Zubrzycki, Geneviève
Abstract: Based on a national survey of U.S. adults conducted six weeks into the COVID-19 pandemic, this article investigates how crisis affects religious faith. Almost no Americans reported losing or a weakening of faith in response to the pandemic at this time. By contrast, nearly one-third of believers indicated that the coronavirus outbreak had strengthened their faith. We theoretically develop and empirically test three religious factors—theodicy, practices, and tradition—to explain variation in the strengthening effect of the COVID-19 pandemic among believers. Results from statistical models show that two theodicic interpretations—believing that God: is using the pandemic as a way to tell humanity to change; and will personally protect you from the virus—significantly increased believers' reports of faith strengthening, controlling for other factors. We also found that Black Protestants were more likely to report these interpretations, which in turn strengthened their faith in response to the pandemic.